Vaginal cytology with suspicion of squamous intraepithelial lesion of undetermined grade: A case report - Almeida, Bruna; Mendonça, Paula; Fagulha, Rita (Citotech Online - Case Review, 2015)
This article reports a case of a 42 year-old female patient diagnosed in 2011 with adenocarcinoma in situ and severe cervical intraepithelial neoplasia that was treated with trachelectomy. In November 2013 a vaginal vault cytology was performed, with cytological findings consistent with low-grade squamous intraepithelial lesion but also with the presence of cells that favour the diagnosis of high-grade intraepithelial lesion. Since it was not possible to grade the lesion as clearly low or high, it was attributed the result of squamous intraepithelial lesion of undetermined grade. In order to confirm and clarify the diagnosis, a biopsy was performed which showed results of severe squamous intraepithelial neoplasia without evidence of stromal invasion. Finally, the specimen was tested for human papillomavirus genotype, with a positive result for type 16. Cytologic diagnosis of intraepithelial lesions of undetermined grade present histologic outcomes that are statistically different from intraepithelial lesions of high and low grade, and are mostly associated with infection by high-risk human papillomavirus. This findings support retaining intraepithelial lesions of undetermined grade as a unique category in the Bethesda System, and define the management guidelines for this patients.